Islamic windows in public conventional banks - a comparative study between Iraqi and Algerian legislation - - Bougassa, Mouad (Dirassat Journal Economic Issue, 2023)
This study aimed to analyze the legal status of Islamic banking, especially Islamic windows, in both Iraq and Algeria, and compare them in order to identify the most important points in which the Algerian legislator can benefit from to develop his Islamic banking experience. This study comes in the midst of the Algerian government’s orientation and support for Islamic banking in order to absorb the monetary mass circulating outside the official regulated market. The study concluded that there is a great similarity between the Iraqi and Algerian legislations on Islamic banking in general, but the Iraqi legislator outperformed his Algerian counterpart in some details that the latter can benefit from, including: the conditions to be met by members of the Sharià committee, permitted and prohibited activities, etc.